Preventiometer, a Novel Wellness Assessment Device, Used With Healthy Volunteers: A Phase 2 Study*. (17th November 2021) - Nanda, Sanjeev; Chon, Tony Y.; Mahapatra, Saswati; Lindeen, Stephanie A.; Fischer, Karen M.; Krüger, Markus; Schierwater, Bernd; Schmidt, Carsten O.; Wahner-Roedler, Dietlind L.; Bauer, Brent A.
Background: We previously reported on a pilot study to assess the incorporation of a novel wellness assessment device, the Preventiometer (iPEx5 GmbH, Greifswald, Germany), into an academic medical practice. The present follow-up study expands on those data and evaluates the acceptability of the assessment process in a larger sample population. Objective: The aim of this study was to evaluate participant satisfaction with the Preventiometer wellness assessment. Methods: A total of 60 healthy volunteers participated. Each participant underwent a comprehensive wellness assessment with the Preventiometer and received data from more than 30 diagnostic tests. A 32-question survey (with a numeric rating scale from 0 to 10) was used to rate the wellness assessment tests and participants' impressions of the wellness assessment. Results: Each assessment had a significantly higher rating than 7 ( P < .001), and the majority of participants agreed or strongly agreed that they were satisfied (98.3%), and they strongly agreed that they were engaged the entire time (93.2%), and liked the instant test results feature of the Preventiometer device (93.2%). Conclusion: This study confirms findings from our previous pilot study regarding the feasibility of the Preventiometer as a wellness assessment tool. The study further demonstrated that 98% of participants were satisfied with the assessment and that all of them would recommend it to others.